Decomposition conditions for two-point boundary value problems - Wenying Feng (International Journal of Mathematics and Mathematical Sciences)
We study the solvability of the equation x″=f(t,x,x′) subject to Dirichlet, Neumann, periodic, and antiperiodic boundary conditions. Under the assumption that f can be suitably decomposed, we prove approximation solvability results for the above equation by applying the abstract continuation type theorem of Petryshyn on A-proper mappings.